The Effect Of A Proposed Educational Program Based On The Principles Of The Pragmatic Theory In The Curriculum In Achieving Cognitive And Social Competencies For The Physical And Sports Education Class In High School - Moussaoui, Alaeddine; Ghribi , Hichem; Cherifi , Walid (sports creativity, 2025)
This study aimed at identifying the effect of a proposed educational program based on the the principles of the pragmatic theory in the curriculum in achieving the cognitive and social competencies of the physical and sports education class, where the researcher assumed that the educational program has a positive effect in achieving the cognitive competencies of the two volleyball, and the relay activities, as well as social competencies represented in raising the degree of social interaction among students during the lesson. The researcher adopted the experimental method by adopting experimental and control group, each group consisted of 15 students of the second year of secondary school, who were selected and divided randomly. After applying the program for 12 weeks, with two sessions per week, the duration of each session is 50mins, And doing the pre and post tests, represented in the social interaction anxiety scale and two cognitive tests in each of the volleyball and the relay activity, It was concluded that the educational program has a positive effect in achieving the cognitive competencies of the relay running activity, as well as raising the level of social interaction among the students, it was also concluded that the experimental and control groups possessed all the components of cognitive competencies related to volleyball activity.